Development of Holistic Assessment Instruments Based on Local Wisdom of Silver Crafts in Kota Gede on Temperature and Heat Topic - Rahmania Amanah Putri; Heru Kuswanto; Edi Istiyono (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2025)
This study aims to develop an assessment instrument based on local wisdom that covers three domains in physics learning: affective, cognitive, and psychomotor domains, especially on temperature and heat topic. This instrument was developed to assess students' understanding of scientific concepts and attitudes after receiving temperature and heat material using interactive e-books, and remains relevant to the demands of the Merdeka Curriculum. The research method uses the Research and Development (R&D) approach with development stages including planning, compilation, validation, and limited trials. Data collection techniques include tests and observations. The cognitive instrument is in the form of a pretest and posttest with multiple-choice item types. The affective instrument is a statement to assess scientific attitudes such as curiosity, critical thinking, creativity, openness to criticism, and cooperation. The psychomotor instrument is in the form of an observation sheet to assess students' presentation skills. The results of the validity and reliability tests show that all instruments are included in the good category and are suitable for use, but improvements are needed in terms of the number of respondents and the number of items to produce higher reliability values. The results of this assessment instrument development not only support instructional practices, but also its primary contribution lies in its ability to evaluate the three domains of student assessment comprehensively, while simultaneously enriching the scientific discourse on holistic assessment based on local wisdom in physics education.